2014
DOI: 10.1007/s10965-014-0598-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing on stress–strain behaviors and performances of β nucleated polypropylene stretched membranes

Abstract: In this article, two β nucleated polypropylene (β-iPP) precursor films were prepared through crystallizing at 110 and 135°C. The differential scanning calorimetry (DSC), wide-angle X-ray diffraction (WAXD), scanning electron microscopy (SEM) and tensile testing were employed to investigate the influence of annealing on stress-strain behaviors and performances of biaxial stretched membranes. The traditional time consuming annealing treatment demonstrates that within the most favorable annealing temperature wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The traditional annealing treatment consumes too much time, for example, the cast film of dry process using uniaxial stretching technique must be annealed offline for about 12 h . In order to improve the efficiency and effect of annealing in the dry process using biaxial stretching technique, we employed the first roller in the longitudinal stretching unit to heat the cast film at high temperature instantaneously . It is clear to see from Figure a that the onset melting temperatures of the cast films annealed for 10 s at 150 °C and 10 s at 155 °C were higher than that annealed conventionally at 140 °C for 2 h. In addition, the melting peaks of β crystals narrowed apparently.…”
Section: Manufacturing Technique Optimization Of Dry Process Separatomentioning
confidence: 99%
“…The traditional annealing treatment consumes too much time, for example, the cast film of dry process using uniaxial stretching technique must be annealed offline for about 12 h . In order to improve the efficiency and effect of annealing in the dry process using biaxial stretching technique, we employed the first roller in the longitudinal stretching unit to heat the cast film at high temperature instantaneously . It is clear to see from Figure a that the onset melting temperatures of the cast films annealed for 10 s at 150 °C and 10 s at 155 °C were higher than that annealed conventionally at 140 °C for 2 h. In addition, the melting peaks of β crystals narrowed apparently.…”
Section: Manufacturing Technique Optimization Of Dry Process Separatomentioning
confidence: 99%
“…For example, Grant et al [24] found that the films annealed near the melting temperature of β crystal exhibited larger porosity, suggesting that annealing perfected the crystalline structure, thereby contributing to the formation of pores. In our previous work, we found that annealing could not only thicken the lamellar thickness but also narrow the lamellar thickness distribution, thus improving the performance of membranes [25]. Yang et al [26] succeeded in improving the pore size distribution by optimizing stretching temperature and tensile ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The dry-stretching process was rapidly developed as a highly efficient industrial method to prepare PP microporous membranes through casting, annealing, stretching process, respectively [2][3][4]. In detail, the dry-stretching process involves three main steps [3,5,6]: (1) preparation of precursor film (cast film) with hard-elastic property (Shish-kebab microstructure [7]) via being uniaxially stretched along the machine direction; (2) thickening of the film's lamellae through annealing process [8]; and (3) stretching along the machine direction of the film at low temperature initially to create the voids and at high temperature subsequently to enlarge the voids. After step (3), the stretched films are heat-set to improve their dimensional stability [9].…”
Section: Introductionmentioning
confidence: 99%